Diesel - saline water separation by coalescence plate - Wong, Kiew Chin (Universiti Malaysia Sarawak, UNIMAS, 2010)
A novel and highly efficient circular phase separator with coalescing medium in counter-current flow was recently developed for treating wastewaters loaded with oil in Malaysia. The coalescing medium consists of 11 layers of inclined dual angle coalescing plates to promote faster rising of oil droplets through coalescence process. By continuous testing the experiment, the oil removal efficiency as higher as 85.2 % can be reached at 0.5 × 10-5 m3/s flowrate. At the same time, Malaysia is both a victim and contribution to oil pollution. As a victim of pollution, Malaysia has long been exposed to the oil tanker traffic and the risk of oil tanker accidents. When the exploration and exploitation of hydrocarbons in the offshore areas started, Malaysia has since become producer of oil pollution, hence exposing the coastal and marine environment to this contamination. This research was use the same circular phase separator DPCC separator to separate oil from oily saline water. It was found that the oil removal efficiency is 38.64% at the 1.5 × 10-5 m3/s flowrate.